Groundwater Potential and Recharge Zone Mapping for Namakkal Town Using RS & GIS - Subramani, T; Santhi, D (International Journal of Engineering and Technology, 2018)
Groundwater is the main source for domestic, industrial and agricultural requirements. Hence the groundwater infected with the aid of anthropogenic activities. Due to the depletion of ground water wells natural recharge will be insufficient to fulfill the actual requirement. The usage of remote sensing and geographic information system (GIS) it's far viable to take quantity of various thematic maps of the identical region and overlay them on top of each other to form a trendy incorporated layer. The thematic layers had been first digitized from satellite imagery, bolstered by using way of auxiliary information, as an example, topo sheets and region investigation facts, at thematic layers had been integrated the using. A contextual evaluation became directed to find out the groundwater capability zones in Namakkal District.Â